Kajian kausal kinerja karyawan, kepuasan kerja, dan burnout - R Junianto; Rony Setiawan (Universitas Kristen Maranatha, 2026)
This research has a main objective, which is to analyze the causes and effects of burnout and job satisfaction on employee performance at the Vehicle Parts Store and Workshop of PT Sumber Langgeng Motor Padalarang. The basis for conducting this research is the urgency of the crucial contribution of employees as the spearhead of direct service to customers in the vehicle maintenance service industry. This research uses a quantitative approach with questionnaires as a survey method for operational employees at the company. The data is analyzed using linear regression to trace employee performance as a result of burnout and job satisfaction, including mediation tests to examine indirect effects. This research successfully proves that burnout does not have a direct effect on employee performance, but it does have a negative effect on job satisfaction. Furthermore, job satisfaction has a positive effect on employee performance. It was found that job satisfaction is a mediator of causality between burnout as a stimulus and employee performance as a response. The company should manage the mental and physical fatigue of employees and also create a work atmosphere that can satisfy employees, so that employee performance can continue to be conducive.